The largest appliqué Buddhist scroll in the collections of the National Museum of the Republic of Tuva - Bicheldey, Ulyana P. (The New Research of Tuva, 2019)
Tuvan craftsmen had been following the traditions of Buddhist iconography since the latter half of the 18th century. Their work has its distinctive local features, setting it apart from the methods employed by their Mongolian counterparts. The Aldan Maadyr National Museum of the Republic of Tuva has in its collections three Buddhist thangkas (iconographic compositions on textile) made in the technique of the appliqué. Among the three, one stands out – a large appliqué image of a Buddhist deity. It is significant both as a valuable source of information on religious culture of the region and as its sacred object. This article for the first time describes some of the understudied relics, also offering a contribution to the studies of Tuva’s religious architecture.Provided are the metadata on each of the three appliqué thangkas (acquisition date, time of creation, description of the imagery), accompanied by their photographs. The largest of the three thangkas were donated to the museum in June 1960, together with a number of other ritual objects confiscated from the prayer yurts of Kyzyl Chyraa in Dzun-Kemchik rayon. Also described is the piece of cloth encasing the appliqué. It features a three-faced deity with four arms clad in a beautiful garment – probably an avatar of bodhisattva Avalokiteśvara (Padmapani) of endless compassion.The article concludes that appliqué could have been made by local craftsmen in Tuva, while the textiles must have come from China.
Keywords: Buddhist religious decorative art; thangka; Buddhist scroll; Buddhist icon; appliqué thangka; National Museum of the Republic of Tuva; Tuva